Statisches und dynamisches Verhalten von aussteifenden Wandscheiben in Brettstapelbauweise - Sandhaas, CarmenBlaß, Hans Joachim (Karlsruher Berichte zum Ingenieurholzbau / Karlsruher Institut für Technologie, Holzbau und Baukonstruktionen, 2016)
Joints and shear walls of buildings made from dowel-laminated timber were experimentally investigated and assessed. Based on cyclic tests on shear walls, a nonlinear dynamic building model was developed. The developed model served to evaluate the seismic behaviour of buildings made from dowel-laminated timber and to derive a preliminary behaviour factor q required for seismic design of this building typology.